Peripheral neuropathy and headache in cancer patients treated with immunotherapy and immuno-oncology combinations: the MOUSEION-02 study. (2nd December 2021) - Rizzo, Alessandro; Santoni, Matteo; Mollica, Veronica; Logullo, Francesco; Rosellini, Matteo; Marchetti, Andrea; Faloppi, Luca; Battelli, Nicola; Massari, Francesco
ABSTRACT: Introduction: Treatment-related neurotoxicity is a common side effect in cancer patients. However, few data are available regarding the risk of several neurotoxicities in patients treated with immune checkpoint inhibitors. Areas covered: The MOUSEION-02 study is an up-to-date meta-analysis aimed at assessing the risk of peripheral neuropathy, peripheral sensory neuropathy, and headache in cancer patients receiving immunotherapy and immuno-oncology combinations. Patients receiving immunotherapy (as monotherapy or in combination with other anticancer agents) showed lower risk of all-grade peripheral neuropathy (RR, 0.50; 95% CI, 0.35–0.70) and all-grade peripheral sensory neuropathy (RR, 0.49; 95% CI, 0.30–0.79). Similarly, in patients treated with immune checkpoint inhibitor monotherapy, we observed lower risk of all-grade peripheral neuropathy (RR, 0.05; 95% CI, 0.03–0.10) and all-grade peripheral sensory neuropathy (RR, 0.11; 95% CI, 0.05–0.23). No differences were observed in terms of all-grade headache. Expert opinion: Although the results of this meta-analysis should be interpreted with caution due to several issues, our study draws attention to immunotherapy-related neurotoxicity with the aim of maximizing clinical outcomes of cancer patients experiencing these not uncommon, and yet poorly studied, adverse events.